Czy w najbliższym czasie powstanie język śląski? - Siuciak, Mirosława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
The article embarks on a critical analysis of the issue, recently reverberating across the country, of granting a status of a regional language to the Silesian ethnolect. Within the relevant public space, the problem interlocks the three following types of discourse: legal, political and scientific. Onto thus formulated discourse superimposesthe common perception of the unresolved tension of the augmented efforts for revival of the self-identity and political positioning in the Silesian society. These efforts are, in turn, related to a very strong feeling of ethnic identity of the Silesians, who like to emphasize their cultural distinctiveness in everyday communicative situations. The notion of the regional language is a special legal category in EU legislation and has been introduced to Polish legislative discourse after this particular language status has been granted to Kashubian. Currently, a number of political and social initiatives are being undertaken in Upper Silesia that are aimed at the administrative recognition and the application of the same legal category to the Silesian ethnolect. As these actions are mainly undertaken by organizations that demand political autonomy for Silesia and put forward demands for the recognition of the Silesian nationality, academic circles are in the main wary, if not apprehensive. As a result, the role of the elite seeking to work out grammatical standards and spelling convention for the Silesian language in the making, being created in a top-down fashion, has been largely taken over by local associations of people wishing to revive the Silesian regional dialect, with a little support of professional and academic staff. Future fortunes of the would-be Silesian language depend on many factors: on whether the legal status of a regional language will be granted or not, on the quality of work of those who have embarked on attempts to carry out agenda that includes works on the standard spelling convention for the language, and on the Silesians themselves and their acceptance of the solutions that are to be imposed in a top-down fashion. Another contributing factor will undoubtedly be the elevation of the Silesian language status through a creation of the language corpus (literature, dictionaries, course books) and broadening of its functional scope.